COVID‐19: An Indian perspective. Issue 5 (22nd November 2020) - Velayudhan, Bashi; Idhrees, Mohammed
Abstract: Lockdown, quarantine, self‐isolation, personal protection equipment, and social distancing have become words of daily usage ever since the world health organization declared coronavirus disease 2019 (COVID‐19) as a pandemic. The impact of COVID‐19 extends over the medical field, economy, education, and politics. Though the knowledge of the virus is evolving, we are yet to find a solution. India, country with the second largest population, went into a phase of lockdown from 25th March 2020 to 31st May 2020. There was phased measure to "Unlock" starting from 1st June 2020. This has affected the clinical practice and training of the resident. The challenges faced during this unprecedented time are multifaceted which includes overcrowding, healthcare system, and educational background. Indian Association of Cardiovascular‐Thoracic Surgeons kept continuing the educational program through a series of "Masterclass."